2018
DOI: 10.1371/journal.pone.0208848
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of surgical outcomes between pre-and full-term patients with exotropia

Abstract: PurposeTo compare the surgical outcomes between pre- and full-term patients with exotropia and to examine the factors associated with surgical outcomes.MethodsThis retrospective study included 48 pre- and 432 full-term patients with basic-type exotropia who underwent unilateral or bilateral lateral rectus muscle (ULR or BLR) recession. Preoperative characteristics and surgical outcomes were compared between the pre- and full-term infants. Additionally, factors affecting the surgical outcomes were evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our model is currently suitable for constant, intermittent, perceptual exotropia and exotropia with a "V" or "A" pattern; subjects with secondary and paralytic strabismus will still require personalized designs by experts. The average difference between the forecast and actual target angles in the retrospective test set was 2.3º (4.7) in all subjects and 2.0º (3.9 PD) in the most popular group (angle=15.0-24.9º), which is smaller than the angle interval of 5 PD for surgical procedures used in most protocols (41,42). As exotropia is the most common subtype of strabismus in China and the primary type found in inpatients who need surgery (4), the operation advice system in our platform may provide substantial help in clinical practice.…”
Section: G Hmentioning
confidence: 76%
See 1 more Smart Citation
“…Our model is currently suitable for constant, intermittent, perceptual exotropia and exotropia with a "V" or "A" pattern; subjects with secondary and paralytic strabismus will still require personalized designs by experts. The average difference between the forecast and actual target angles in the retrospective test set was 2.3º (4.7) in all subjects and 2.0º (3.9 PD) in the most popular group (angle=15.0-24.9º), which is smaller than the angle interval of 5 PD for surgical procedures used in most protocols (41,42). As exotropia is the most common subtype of strabismus in China and the primary type found in inpatients who need surgery (4), the operation advice system in our platform may provide substantial help in clinical practice.…”
Section: G Hmentioning
confidence: 76%
“…The target angle is derived from the measurement of deviation in different circumstances (e.g., deviation with either eye staring forward). The second step is the choice of the surgical technique (e.g., bilateral lateral rectus muscle recessions or unilateral recession and resection) (8,39,40) and surgical dose (39,41,42), which may vary according to the preoperative diagnosis, the angle of deviation at distance and near, the anatomy of the extraocular muscle, physician preference and experience (8). The procedure was undertaken using the surgical dose at the authors' clinic as shown in Table 2.…”
Section: G Hmentioning
confidence: 99%
“…This significantly high number of preterm patients having neurodevelopmental disabilities is also described in a study by Jung et al . [ 23 ]…”
Section: Discussionmentioning
confidence: 99%